(untitled) (World Bulletin of Management and Law, 2026)
The rapid development of digital technologies has significantly influenced the content and forms of legal relations, including the institution of representation. Digital representation refers to the granting and exercise of authority through electronic documents, information systems, and electronic digital signatures. This article analyzes the key trends in the development of legislation on digital representation and reveals its legal nature. The study provides a comparative analysis of foreign legal experience and the legislation of the Republic of Uzbekistan, highlighting the stages of formation of digital representation. Special attention is given to the legal role of electronic documents and electronic signatures in representative relations. The research substantiates the need to further improve legislation by clearly defining the legal status of electronic powers of attorney and digital authorization mechanisms. The findings of the article are significant for enhancing digital legal relations and may be applied in legal practice.